Prospective, controlled study of invasiveness and post-aggression metabolism in patients undergoing robotic-assisted radical prostatectomy - Martinschek, Andreas; Ritter, Manuel; Heinrich, Elmar (Urologia internationalis, 2017)
Objectives: To evaluate in a prospective, controlled, nonrandomized study the surgical stress and acute-phase systemic response in robotic-assisted laparoscopic prostatectomy (RALP) compared to open radical retro-pubic prostatectomy (ORRP) by measuring humoral mediators. Methods: Forty consecutive patients undergoing either RALP or ORRP were prospectively included to assess the extent of systemic response. Blood samples were collected before surgery (T1), at the time of prostatectomy (T2), at the time of wound closure (T3), and 12 h (T4), 24 h (T5), and 48 h (T6) after surgery, and assayed for interleukins (IL-6 and IL-10), C-reactive protein (CRP), and hemoglobin. A 2-sided p < 0.05 was considered to indicate significance. Results: Baseline levels of IL-6, IL-10, and CRP were comparable in both arms of the study. IL-6 and IL-10 increased in both groups during surgery and reached maximum levels at 12 and 24 h after surgery. The RALP and RRP groups differed significantly at T2 (p = 0.009), T3 (p = 0.046), T5 (p = 0.05) and T6 (p = 0.0007) for IL-6, and at T3 (p = 0.05) and T4 (p = 0.05) for IL-10. CRP levels differed significantly at 48 h postoperative (p = 0.0053). The maximum levels of all 3 mediators in the RALP group were significantly lower than those in the open surgery group. Patients in the RALP group experienced less pain from day 2 to 4 according to the Visual Analog Scale (p < 0.05). Conclusions: The study suggests that IL-6 and IL-10 are useful objective markers for surgical stress and that tissue trauma and activation of post-aggression metabolism seem to be less in RALP compared to ORRP.
Gesehen am 13.09.2018